Determinants of Bank’s Profitability: Evidence from Bangladesh - Jahan, Nusrat (Indian Journal of Finance, 2012)
This empirical study was conducted on randomly selected six commercial banks of Bangladesh. This study uses widely used determinants of banks’ profitabilities, which are ROA, ROE and ROD and these are also commonly used criterion of Bangladesh Bank to evaluate banks’ performance. In addition, this study evaluates the efficiency ratio, asset utilization ratio, asset size and ROD as a determinant of banks’ profitability measured by ROA. The results of the financial indicators reveal that the Prime Bank is considered to be out performing in terms of total assets, whereas Arab Bangladesh Bank is showing soaring performance in terms of profitability. The results of regression analysis found the explanatory variables - operational efficiency, asset size and ROD to be positively related and asset utilization to be negatively related to ROA, but these associations are statistically insignificant.